2019
DOI: 10.1001/jamapsychiatry.2018.3070
|View full text |Cite
|
Sign up to set email alerts
|

Different Types and Acceptability of Psychotherapies for Acute Anxiety Disorders in Children and Adolescents

Abstract: Key Points Question What is the best psychotherapeutic approach for anxiety disorders in children and adolescents in terms of efficacy and acceptability? Findings This network meta-analysis included 101 unique trials with 6625 unique participants who received 11 different psychotherapies and 4 control conditions. Only group cognitive behavioral therapy was significantly more effective in reducing anxiety symptoms than other psychotherapies and all control c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 53 publications
5
64
0
1
Order By: Relevance
“…Regarding efficacy, the results suggested that, compared with the WL control condition, parent-only CBT is an effective treatment for reducing anxiety symptoms and relieving anxiety in children, leading to remission at the end of treatment. The findings in this pair-wise meta-analysis were consistent with a previously reported network meta-analysis [25]. The network meta-analysis included studies in which more than 20% of children took psychotropic drugs, and revealed that parent-only CBT led to better outcomes than WL control condition in children with various types of anxiety disorders.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Regarding efficacy, the results suggested that, compared with the WL control condition, parent-only CBT is an effective treatment for reducing anxiety symptoms and relieving anxiety in children, leading to remission at the end of treatment. The findings in this pair-wise meta-analysis were consistent with a previously reported network meta-analysis [25]. The network meta-analysis included studies in which more than 20% of children took psychotropic drugs, and revealed that parent-only CBT led to better outcomes than WL control condition in children with various types of anxiety disorders.…”
Section: Discussionsupporting
confidence: 89%
“…Comparison of parent-only CBT with CBT involving parents revealed the same efficacy of the two treatments. According to previous studies [25,26], CBT involving parents was effective for treating child anxiety disorders. Particularly for early childhood anxiety, CBT involving parents is reported to be more beneficial for young children than for older children because of their limited language and cognitive competence [27].…”
Section: Discussionmentioning
confidence: 99%
“…Where previous reviews have considered outcomes in relation to parent involvement (e.g. Zhou, Zhang, Furukawa, Cuijpers et al 2019 ; Reynolds et al 2012 ), they have not focused specifically on adolescents or anxiety disorders. In reviews of treatment for younger children or across broad age ranges, there have been mixed findings for whether parental involvement improves outcome (Reynolds et al 2012 ; Thulin et al 2014 ); however, there is some indication that where parental involvement includes contingency management or transfer of control, this has a beneficial effect on child outcome at follow-up (Manassis et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Where studies focus specifically on adolescents, the majority of RCTs have involved young people with primary social anxiety disorder (e.g. 62% of adolescent studies in Zhou et al, ) and those with large effect sizes have tended to include young people identified through screening in schools and include sessions within and outside schools to practice social skills (Masia Warner, Fisher, Shrout, Rathor, & Klein, ; Masia‐Warner et al, ). Given these trials involve young people who are regularly attending school, it is unclear to what extent the findings will extend to those young people who experience high avoidance (and potentially symptom severity) which has led to difficulties attending school.…”
Section: Treatment: Psychological Interventionsmentioning
confidence: 99%